Association of intestinal microbiota with anxiety and depression disorder (Research, Society and Development, 2021)
Introduction: The psychosocial stress that people experience daily is an important factor in the cause of mental illnesses such as depression and anxiety through stress. When they are not properly treated, due to the mental impossibility of not being able to express these problems, these diseases can manifest in the body through psychosomatic symptoms. Methodology: This is an integrative review, a search was conducted in the SciElo, LILACS and Pub Med databases, and the following words were used for the databases: “intestinal microbiota” “Depressive disorder” and “Anxiety Disorder”. The articles identified during the search in the databases were selected from the reading of the titles, followed by the abstracts, including 5 articles in the study. Results: The studies were selected according to the authors, the year of publication, place of study, type of study, results and conclusion. The relationship between intestinal microbiota and human health has been restricted to the most common mental and  behavioral disorders. Final Considerations: It was concluded that it is important to emphasize the importance of conducting studies on this topic, with the aim of contributing to the quality of life of people who have these disorders.